INTERFERÊNCIA DA CLASSIFICAÇÃO E DO ARMAZENAMENTO NA QUALIDADE DE SEMENTES DE CEVADA - Waureck, Ariadne (2015)
The seeds classification and the appropriate storage conditions are critical to maintaining quality, otherwise, the previous efforts to develop material and cultural techniques for seed production will not be valid. Accordingly, the objective of this study was to evaluate the interference of classification and storage on quality of barley seeds. Seed samples of four lots of BRS Cauê were used. The design was completely randomized with the treatments: group I - control - seeds unclassified; treatment II - seeds retained on the sieve 2.2 mm width x length 22.0mm; treatment III - seeds retained on the sieve 2.2 mm width x length 22.0mm + table of gravity; IV treatment - seeds retained on the sieve 2.5 mm width x length 22.0mm; treatment V - seeds retained on the sieve 2.5 mm width x length 22.0mm + table gravity. The evaluations were performed at the beginning of storage and 45, 90 , 150, 210 and 270 days after storage. The seeds remained stored in natural environment. To determine the quality of seeds were evaluated: the water content , the volumetric weight, thousand seed weight , the amount of infected seeds, germination, vigor, health and protein content. The infestation , test weight , moisture content and protein content , were not subjected to statistical analysis , the first three repetitions performed with two replications . The results of percentage of sanity test were transformed into arcsin √ ( x / 100 ) , and the other variables were subjected to analysis of variance and means were compared by Tukey test at 5 % significance level. In general, the results of seeds classified in sieve 2.5 x 22.0 mm associated with gravity table presented thousand seed weight and higher test weight in relation to the results of other treatments. However, these results were not observed for physiological and health parameters and protein content . Thus, it is concluded that , right for the barley seeds is the classification in the sieve 2.5 mm + table gravity. Besides, there was a reduction in the quality of barley seeds and the incidence of field fungi from 90 days of storage in a natural environment .